Proteogenomic annotation of T6SS components identified in Bacteroides fragilis secretome - Zakharzhevskaya, Natalya B.; Shagaleeva, Olga Yu; Kashatnikova, Daria A.; Goncharov, Anton O.; Evsyutina, Daria V.; Kardonsky, Dmitry A.; Vorobeva, Elizaveta A.; Silantiev, Artemiy S.; Kazakova, Viktoria D.; Kolesnikova, Irina V.; Butenko, Ivan O.; Vanyushkina, Anna A.; et al. (Frontiers in Microbiology, 2025)
IntroductionBacteroides fragilis (Bf)’s T6SS locus has been characterized and shown to have functional activity in competition experiments. It has been demonstrated that symbiont nontoxigenic Bf strains have a more effective “weapon” effect on pathogenic Bf, which is realized through the activity of effector-immune (E-I) protein pairs. Intensive study of the T6SS structure has led to an understanding of certain issues related to its functional activity, but the exact regulatory mechanisms of E-I protein pair activity remain unclear. Proteomic annotation of T6SS components and detailed descriptions of all immune-effector pairs are currently available. In this research, we performed detailed proteogenomic analysis and subsequent proteomic annotation of the T6SS components of the toxigenic Bf BOB25.Material and methodsFractionated cells, cultivated media and vesicles were prepared for proteome analysis by HPLC-MS/MS. Proteogenomic annotation and comparative genomic study of the T6SS loci of the toxigenic Bf BOB25 were carried out by comparison with the reference genomes of the following Bf strains: JIM10, NCTC 9343 and 638R.ResultsAccording to the data obtained, T6SS components were represented in all types of the analysed samples. The following components of the T6SS were identified in culture media and cells: ClpV (TssH), TssK, TssC, TssB, Hcp (TssD), and TetR. The predicted effector protein AKA51715.1 (VU15_08315) was also detected in media. The greatest amount of T6SS proteins, including the Hcp protein, was detected in the vesicle samples, which was also observed by TEM. Potential effectors, including AKA51715.1 (VU15_08315), AKA51716.1 (VU15_08320), AKA51728.1 (VU15_08385) and the immune protein AKA51727.1 (VU15_08380), were detected in vesicles.DiscussionThe presence of the immune and effector proteins in the Bf secretome indicates the high activity of the T6SS without bacterial competition. It is possible that the T6SS is also used by bacteria to regulate population size by altering the activity of different repertoires of E-I pairs.